Unmasking Marlina: psychoanalytic perspectives on women's supremacy and subordination in Indonesian cinema - Setiawan, Bayu; Wulandari, Sri; Ridlo, M. Harun Rosyid (Gelar: Jurnal Seni Budaya, 2024)
This research aims to explore the unconscious motivations and character development portrayed in the film "Marlina, the Murderer in Four Acts" through a psychoanalytic point of view. The objectives include analyzing the visual attributes and emotional states of the character Marlina, categorizing them into complex emotions, and examining the relation between supremacy and subordination along the film storyline. By conducting a detailed visual psychoanalytic approach, integrating psychological theories and visual analysis techniques. Data collection was conducted by observing and interpreting visual attributes such as shot types, camera angles, character actions, and environmental situations in all scenes Marlina portrayed. The findings reveal how Marlina's unconscious emotional states are intricately reciprocal interactions with the male characters. Also about how supremacy and subordination are signified by her resistance against patriarchal oppression in more complex emotional states. The research highlights the method to do psychoanalytic analysis in understanding character emotion and narrative construction in cinematic works, while also focusing on approaches to explore the complexities of human emotion and behavior in film work.